Negotiating social norms, the legacy of vertical health initiatives and contradicting health policies: a qualitative study of health professionals’ perceptions and attitudes of providing adolescent sexual and reproductive health care in Arusha and Kilimanjaro region, Tanzania - Sara Bylund; Mats Målqvist; Nosim Peter; Sibylle Herzig van Wees (Global Health Action, 2020)
Background Adolescents in Tanzania are at risk of many health problems attributed to limited access to quality sexual and reproductive health services. Health professionals are a crucial part of service delivery, and their perspective on providing care is important in understanding the barriers that hamper access to sexual and reproductive health services for adolescents. Better understanding these barriers will support the development of more effective interventions. This paper explores these perspectives in view of the health-policy context that surrounds them. Objective This study has aimed to explore and understand health professionals’ perceptions and attitudes regarding the provision of adolescent sexual and reproductive health care in a selected national sexual and reproductive health programme in the Arusha region and Kilimanjaro region, Tanzania. Methods A qualitative cross-sectional interview design was applied. Sixteen in-depth interviews were conducted with health professionals and community health workers. Data was analysed following inductive thematic analysis. Results Four main themes are identified in the data: concern about the stigma directed towards adolescents; over-medicalisation of services; difficulty involving adolescent males; and ambiguous policies and contradictory messages. The findings suggest that health professionals providing care in the current adolescent sexual and reproductive health programme must navigate the legacy of vertical health programmes as well as contradicting views and messages that are influenced by social norms, by uncertainties about current laws and by statements from political leaders. Conclusions The findings suggest that future research, policies and health programmes should consider the perspectives of health professionals and their challenges in delivering care for adolescents to help improve the understanding of how to effectively and sensitively implement sexual and reproductive health programmes for adolescents.